PJMHS 2021
DOI: 10.53350/pjmhs211571864
|View full text |Cite
|
Sign up to set email alerts
|

Determine the Impact of Prone Positioning in Covid-19 Patients

Abstract: Objective:To determine the effectiveness of prone positioning in patients of covid-19 deisease presented with respiratory failure. Study Design: Retrospective/Observational study Place and Duration: Medicine department of BKMC/MMC, Mardan and Mohiuddin Teaching Hospital, Mirpur AJK for six months during the period from August 2020 to January 2021. Methods: Total 100 patients of respiratory failure admitted to ICU were included in this study. Patients detailed demographics age,sex and body mass index were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Our results were comparable to the previous researches. [18,19] We found that 55 (64.7%) patients had moderate disease while 30 (35.3%) had severity of disease among all cases. [18] Symptoms such as fever, cough, and dyspnea were the most often reported in both groups.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our results were comparable to the previous researches. [18,19] We found that 55 (64.7%) patients had moderate disease while 30 (35.3%) had severity of disease among all cases. [18] Symptoms such as fever, cough, and dyspnea were the most often reported in both groups.…”
Section: Discussionmentioning
confidence: 69%
“…[18,19] We found that 55 (64.7%) patients had moderate disease while 30 (35.3%) had severity of disease among all cases. [18] Symptoms such as fever, cough, and dyspnea were the most often reported in both groups. The majority of patients showed bilateral lung involvement with interstitial infiltrates, followed by consolidation and unilateral infiltrates, according to the findings.…”
Section: Discussionmentioning
confidence: 69%